1971
DOI: 10.3171/jns.1971.34.3.0432
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous disappearance of cerebral arteriovenous angioma

Abstract: ✓ The author reports a case in which a cerebral arteriovenous malformation disappeared completely and spontaneously within 3 years. Comparable cases from the literature are cited. The disappearance of the malformation may have been due to hemorrhagic episodes and the resulting thromboses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Seventy ®ve percent of our patients had small AVMs and showed single venous drainage. In [2,3,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. However, in our brain AVM database, the spontaneous regression had occurred in only about 0.6% of small (<3 cm) brain AVMs (3/474), and AVMs with multiple draining veins can also progress to spontaneous regression [6,10,11,20].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Seventy ®ve percent of our patients had small AVMs and showed single venous drainage. In [2,3,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. However, in our brain AVM database, the spontaneous regression had occurred in only about 0.6% of small (<3 cm) brain AVMs (3/474), and AVMs with multiple draining veins can also progress to spontaneous regression [6,10,11,20].…”
Section: Discussionmentioning
confidence: 70%
“…They include mass eect on the feeding arteries from an intracranial hematoma or associated edema [3,6,7,9,16,18] or feeding arterial occlusion due to atherosclerosis [2], thromboembolism [17] or systemic coagulation disorders [4]. However, if the feeding arteries are completely occluded by any etiological condition, the AVM can recruit arterial collaterals through a non-sprouting angiogenesis if the shunt remains patent [1].…”
Section: Hypotheses For Spontaneous Regression Of the Cerebral Arterimentioning
confidence: 99%
“…Spontaneous thrombosis and regression of AVMs have been recog nized in our own experience and that of others [12] but its incidence remains unknown. This phenomenon may have been favorably influenced by radiation delivery in a few select cases.…”
Section: Discussionmentioning
confidence: 99%
“…18,24,27,47,64,72,75,76,80,81,85,86,90,112,116,118 One series of 106 patients with AVMs has demonstrated that > 50% of the lesions increased in size, whereas 9% decreased over a mean period of 8 years without intervention. Remodeling within these lesions can lead to changes in their angiographic appearance over time.…”
mentioning
confidence: 99%